Analyzing riparian zone ecosystem services bundles to instruct river management. Issue 1 (1st January 2017) - Van Looy, Kris; Tormos, Thierry; Souchon, Yves; Gilvear, David
ABSTRACT: The ecosystem service framework is now well accepted for focussing management strategies to preserve and restore ecosystems. Its implementation remains challenging, however, due to the environment's complexity and dynamics that interfere with ecosystems' ability to provide the services. Here, we question whether we can show where and how to intervene in riparian corridors to restore specific ecosystem services without endangering others. Specific hypotheses in this context are for the spatial aggregation of ecosystem services delivered by riparian corridors with respect to naturalness (1), to the existence of bundles of ecosystem services (2), and finally for the scale sensitivity of this congruence (3). Within a Geographical Information System framework, we analyse the capacity of riparian corridors to provide ecosystem services over three river basins in the Bresse region (France) based on high-resolution data of the riparian corridor hydromorphology and land use. Specifically, we compare the capacity to provide two services: in-stream water purification and riparian retention of nutrients that are critical goals for river management and rehabilitation strategies. We observe little spatial association and high spatial variability for the two emphasized ecosystem services. Surprisingly, no congruence of ecosystem services with riparian corridor naturalness is present. The absence of associations between ecosystem services and their spatial variability will oblige environmental managers to identify underpinning environmental processes and patterns at local scales. In conclusion, we plead for fine-grained multifunctional assessment of ecosystems' capacity to deliver services, especially in environments such as river corridors that exhibit high environmental heterogeneity.EDITED BY Neville Crossman